The Influence of Strategic Management on Business Performance Based on Competitive Advantage - Flore Cita Simamora (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the influence of strategic management on business performance by considering the role of competitive advantage as a mediating variable. The study used a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to 100 respondents who were managers or company leaders. The data analysis techniques used were multiple linear regression and path analysis with the help of statistical software. The results of the study indicate that strategic management has a positive and significant effect on competitive advantage. In addition, competitive advantage has also been shown to have a significant effect on business performance. Strategic management directly influences business performance, but the indirect effect through competitive advantage is proven to be stronger. This indicates that competitive advantage acts as a mediating variable that strengthens the relationship between strategic management and business performance. The coefficient of determination value indicates that business performance can be significantly explained by strategic management and competitive advantage, while the remaining is influenced by other factors outside the research model. Thus, this study emphasizes the importance of implementing effective and sustainable strategic management in creating competitive advantage to improve company business performance.